Genetics of house mice (Mus domesticus) on the Isle of May, Scotland - Fenton, Michael (2018)
The Isle of May hosts a unique population of house mice, Mus domesticus, following an artificial introduction of Eday mice onto the island 35 years previously. DNA from the uniparentally inherited Sry gene on the Y chromosome and D-loop region in the mitochondrial genome was sequenced from mice from the Isle of May, Eday, nearby Inchkeith and mainland Tollerton, in order to identify SNPs for use as molecular markers. These would be used to distinguish mice of different parental origin, for the purpose of investigating associations between different haplotypes in the Isle of May mice and variation in immune function, and to confirm earlier phylogenetic work on the population using updated techniques. It was suspected that mice of different parental origin had the potential to be exhibiting behavioural and fitness differences such that they may be segregating to different parts of the island whereupon differential selection pressures could act to shape their immune variation. Ruling out such possibilities enables the visible impact of other environmental factors to be magnified and their effect on immune function understood. The Sry gene failed to yield a significant amount of polymorphism between mice of different locations, and as such, investigations were instead focused on detecting population structuring in the population. This was done via analysis of a panel of immune SNPs which could be considered effectively neutral where genetic drift outweighs selection, as Is often the case in small populations such as the Isle of May. Population genetics analysis yielded conflicting results from the Bayesian clustering program STRUCTURE, and an isolation by distance plot produced a negative correlation between genetic distance (1/(1-Fst)) and linear geographic distance, the opposite way to expected. There was not enough sufficient evidence to confirm that the population may be sub-structured, and reject a null hypothesis of panmixia. However, the genetic dynamics of this population are far from clear. Such results may be circumvented through principal components analysis, which may more reliably detect subtle structuring in this feral mouse population.